KARAKTERISASI DAN ESTIMASI SUMBER DAYA GAMBUT SEBAGAI MATERIAL ADSORBEN LOGAM BERAT DALAM LARUTANDI BLOK TELUK MERANTI, KABUPATEN PELALAWAN, PROVINSI RIAU: CHARACTERIZATION AND RESOURCES ESTIMATION OF PEAT DEPOSIT AS HEAVY METAL ADSORBENT IN SOLUTIONAT TELUK MERANTI BLOCK, PELALAWAN REGENCY, RIAU PROVINCE - Muhammad Arief Pinandita; Galuh Yuliani; Agus Subarnas; Denni Widhiyatna; Maryono; Siska Mutiara (Buletin Sumber Daya Geologi, 2020)
Indonesia has the largest peat area in the tropical zone, which represents 70% of the peat area in Southeast Asia and 50% of the world's tropical peatlands. At present, the utilization of peat is still relatively low and its likelihood to cause major fires during dry season is still of great concern in Indonesia. On the other hand, peat has potential to be used as natural adsorbent. This study aims to characterize the adsorptive properties of peat and to estimate its possibleresources as natural heavy metal adsorbent in the Teluk Meranti Block. Peat characterization was carried out by selecting three peat samples, namely PL-13, PL-21 and PL-26 based on elemental analyses. The characterization of BET surface area showed that PL-13, PL-21, and PL-26 have maximum area of 241,73 m2/g, 241,80 m2/g dan 247,29 m2/g, respectively. The adsorption test results show that PL-13, PL-21, and PL-26 have maximum capacity of 15.06; 11.99; and 22.93 mg/g, with adsorption efficiencies of 46.79%; 48.36%; and 46.85%, respectively. Based on Government Regulation No. 57 of 2016, peat with a thickness of three meters or more is determined as protection function of the peat ecosystem. Accordingly, the inferred resources of peat deposits that can be utilized as adsorbent is estimated to be 90,477,890 tonnes.